Hubungan Gaya Kepemimpinan Terhadap Kinerja Perawat di Puskesmas Ridge - Nursyamsiyah Nursyamsiyah; Nur Qamariyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
Leadership is an activity used to influence the behavior of other people so that they are willing to be directed to achieve certain goals, one of which is improving the performance of nursing services. Performance is an effort made from the results of work that can be achieved by a person or group of people in an organization in accordance with their respective authorities. This research method uses an analytical observational research design with a cross sectional study approach. The research population was all nurses at the Ridge Community Health Center, totaling 55 people with a sample size of 55 people, the sampling technique used total sampling technique. The instrument used for data collection was a questionnaire. The research results showed that the majority of respondents were women (72.7%) with a D3 education (76.4%) aged 21-30 years (40.0%) with a length of work of 1-10 years (52.7%). The results of statistical tests show that there is no relationship between authoritarian (p=0.185) and democratic (p=0.128) leadership styles on nurse performance. Meanwhile, there is a relationship between participative leadership style (p=0.000) and Laizes Faire (p=0.000) on nurse performance. Based on the research that has been carried out, it can be concluded that at the Ridge Community Health Center, the Participative Leadership Style (p=0.000) and Laizes Faire (p=0.000) are implemented, resulting in greater performance of good nurses compared to less good performance of nurses.